2017
DOI: 10.1002/jmri.25799
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of in vivo magnetic resonance imaging T1rho and T2 relaxation time measurements of hip cartilage at 3.0T in healthy volunteers

Abstract: 2 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;47:1022-1033.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 35 publications
2
25
2
Order By: Relevance
“…in vivo reproducibility is affected not only by the intrinsic reproducibility of the technique, but also by subject and slice positioning, and segmentation. A recent in vivo reproducibility study reported 6% intrascanner variability for hip cartilage T 2 , whereas for our technique both intra‐ and interscanner T 2 variability were below 6%. Bittersohl et al repeatedly scanned 15 asymptomatic volunteers and reported 3.7–6.8% variability for the mean T 1 in the hip cartilage, whereas we found nearly perfect T 1 reproducibility.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…in vivo reproducibility is affected not only by the intrinsic reproducibility of the technique, but also by subject and slice positioning, and segmentation. A recent in vivo reproducibility study reported 6% intrascanner variability for hip cartilage T 2 , whereas for our technique both intra‐ and interscanner T 2 variability were below 6%. Bittersohl et al repeatedly scanned 15 asymptomatic volunteers and reported 3.7–6.8% variability for the mean T 1 in the hip cartilage, whereas we found nearly perfect T 1 reproducibility.…”
Section: Discussioncontrasting
confidence: 52%
“…Our technique simultaneously yields high‐resolution PD, T 1 , and T 2 maps for six radial sections of the hip in 7:13 minutes, or 1:12 minutes scan time per slice when used in an interleaved multislice protocol. Previous work reported 17:41 minutes to acquire a single coronal T 2 map of the hip with 0.3 × 0.3 × 4.0 mm 3 resolution, and 11 minutes to acquire a 3D sagittal T 2 map of the hip with 0.4 × 0.4 × 1.5 mm 3 resolution . A scan time of ~9 minutes was reported for 3D T 1 mapping of the hip at 1.5 T with 0.8 mm isotropic resolution .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning body mass index, literature shows contradictory results. A recent study found correlation between body mass index and T 1ρ in the knee [38] while others decline a relation between body mass index and T 1ρ values in hip cartilage and intervertebral disc cartilage, respectively [39,40]. In our study, body mass index was not correlated to T 1ρ values.…”
Section: Discussioncontrasting
confidence: 81%
“…An MRF‐based methodology was introduced to acquire PD, T 1 , and T 2 relaxation time maps along radial sections of the hip based on the plug‐n‐play (PnP‐MRF) method . This method's resolution was within the range of resolutions presented in previous hip mapping methods, with an overall faster scan time.…”
Section: Potential Clinical Usesmentioning
confidence: 99%